High Yield of Melanin Production by the Strain Rhizobium sp. R 593 in Liquid State Fermentation - Zhao, Shi-Hao; Tong-Suo, M.A. (Asian Journal of Chemistry, 2011)
In this study, the medium composition and culture conditions for melanin production were investigated by the strain Rhizobium sp. R 593. The significant factors such as L-tyrosine, yeast extract and CuSO4·5H2O in the medium were selected by Plackett-Burman design and then these three factors was further optimized by the steepest ascent and central composite design and analyzed by response surface methodology and the optimum level of the factors were calculated and confirmed by experiments. The values of L-tyrosine, yeast extract, CuSO4·7H2O were 1.15, 2.62 and 0.027 g/L, respectively and the melanin production reached 3.64 g/L under the optimized medium, which was of 1.8 folds of the initial yield.